Overview on HTLV-1 p12, p8, p30, p13: accomplices in persistent infection and viral pathogenesis - Nicot, Christophe; bai, xue tao (Frontiers in Microbiology, 2012)
The human T-lymphotropic virus type-1 (HTLV-1) is etiologically linked to adult T-cell leukemia/lymphoma (ATLL) and tropical spastic paraparesis/ HTLV-1 associated myelopathy (TSP/HAM). While the role of Tax and Rex in viral replication and pathogenesis has been extensively studied, recent evidence suggests that additional viral proteins are essential for the virus life cycle in vivo. In this review, we will summarize possible molecular mechanisms evoked in the literature to explain how p12, p8, p30 and p13 facilitate persistent viral infection of the host. We will explore several stratagems used by HTLV-I accessory genes to escape immune surveillance, to establish latency and to deregulate cell cycle and apoptosis to participate in virus-mediated cellular transformation.